Thermal maturity of Oligocene oil-source rocks in the Cuu Long basin Vietnam: An approach using the illitization of smectite - Vu The Anh; Tran Van Nhuan; Yungoo Song (Petrovietnam Journal, 2012)
The natural transformation of smectite-to-illite in Oligocene-Miocene sediments collected from an exploration well in Block 16-1, Cuu Long basin, has been examined in relation to quartz cementation and thermal maturity of source rocks. Evidences including X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) data, identified that smectite is unstable with increasing burial temperature. Consequently, during the diagenesis stage, it was transformed to illite and released a significant amount of silica which formed micro-crystalline authigenic quartz within the clay matrix. The kinetic equation of the transformation of smectite to illite was utilized to evaluate the maximum paleotemperature for the first time; this indicated that the sediments had experienced a diagenesis episode in which the temperature was in a range of 100 - 140°C.